The e-health Accelerator: Defining End User Needs - Mattie, Johanne; Flegal, Christine; Wong, Angie (CMBES Proceedings, 2010)
The BCIT e-health Accelerator aims to help small and medium sized e-health vendors better understand the strengths and weaknesses of their products in terms of usability and end user (physician, patient, health professional) needs. The Accelerator aims to help Canadian developers bring competitive e-health products to market, improve the quality of Canadian e-health technologies, and improve access of Canadian health care professionals to cutting edge e-health technologies. The Living Lab simulation facility at the heart of this initiative contains a large open space that can be configured to resemble any built environment. Here, potential users can evaluate technology within a realistic setting, thereby providing more realistic results. With funding from NRC-IRAP, a number of different e-health technologies have been evaluated. Evaluations focused on working with end users to better understand their specific e-health technology needs, the barriers that must be overcome to successfully integrate these technologies, and what could be done to increase the adoption of these technologies. As a case study, this presentation will discuss the evaluation of a remote patient monitoring device. Seniors with chronic illness were invited to the Lab to participate in a simulation that included the collection of data from two physiological monitoring devices, a remote video consultation, and a home safety application. Evaluation methods included video and audio recording, observation, semi-structured interviews, and written questionnaires. At the time of abstract submission, this work is still in progress. Results, conclusions and recommendations will be presented at the conference.